THE STATE OF THE PROBLEM OF COGNITIVE FORMATION ACTIVITIES IN THE PRACTICE OF WORK SECONDARY SCHOOLS (Pedagogy of Higher and Secondary Education, 2006)
The article is dedicated to the problem of forming of the activity ofpupils cognitive work in the practice of secondary schools.